PICTURE SERIES IN TEACHING WRITING RECOUNT TEXT TOWARDS THE STUDENTS WRITING ABILITY (Prosiding Seminar Nasional Pendidikan Universitas Subang (SENDINUSA), 2022)
Recount text is one of text types that should be comprehended because it is considered as a difficult text. Recount text has its own generic structure for instance orientation , events , and re-orientation . The subject matter will be more fun, effective, and efficient if the right techniques are used. In the learning process, picture series was chosen as one of the effective techniques to overcome students' writing difficulties. Pictures are one of the most effective tools and stimuli to improve students' skills. Many students are hesitant to write because they believe it is a difficult English skill. Students frequently lack ideas for what they should write about. Furthermore, they find it difficult to tell the next plot or event after writing the introduction paragraph. As a result, English teachers must devise and implement appealing methods for teaching writing recount text. In this case, the teacher can apply and teach students to write recount text using picture series. Its goal is to help students understand and improve their writing skills.
Keywords: Recount Text; Picture; writing